2012
DOI: 10.1002/stc.1530
|View full text |Cite
|
Sign up to set email alerts
|

Symbolization-based differential evolution strategy for identification of structural parameters

Abstract: SUMMARY This new method of identifying structural parameters, called ‘symbolization‐based differential evolution strategy’ (SDES), merges the advantages of symbolic time series analysis and differential evolution (DE). Data symbolization in SDES alleviates the effects of harmful noise. SDES was numerically compared with particle swarm optimization and DE on raw acceleration data. These simulations revealed that SDES provided better estimates of structural parameters when the data were contaminated by noise. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…In fact, the state of the art of these methods has been reviewed in a number of works . According to most of these works, system identification methods can be classified as parametric and non‐parametric (genetic algorithms , evolutionary strategy , neural networks or least‐squares estimation ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the state of the art of these methods has been reviewed in a number of works . According to most of these works, system identification methods can be classified as parametric and non‐parametric (genetic algorithms , evolutionary strategy , neural networks or least‐squares estimation ).…”
Section: Introductionmentioning
confidence: 99%
“…Symbolic time series analysis allows capturing the main features of the underlying system whilst alleviating the effects of harmful noise. The effectiveness of STSA in noisy condition has been demonstrated in several researches [25][26][27]. The results of research presented in [25] show that compared with artificial NN-based method and support vector machine-based method, STSA-based approach provides more robust damage indices in presence of measurement noise.…”
Section: A Background On Symbolic Time Series Analysismentioning
confidence: 98%
“…The effectiveness of STSA in noisy condition has been demonstrated in several researches [25][26][27]. The results of research presented in [25] show that compared with artificial NN-based method and support vector machine-based method, STSA-based approach provides more robust damage indices in presence of measurement noise. In another research, it has been indicated that symbolization can reduce sensitivity to measurement noise [26].…”
Section: A Background On Symbolic Time Series Analysismentioning
confidence: 98%
“…One possible solution maybe substructure level damage identification adapted to the characteristics of each part, for instance, the cable and deck together for the suspension bridge. Furthermore, the damage is basically a local phenomenon, the damage detection methods based on the direct identification of local physical parameters, for instance, the stiffness and damping coefficients (Zhan et al 2014, Nayeri et al 2008, statistical properties of structural responses (Li et al 2013, Alamdari et al 2015 and wave propagation based methods may be feasible (Mohammadtaghi et al 2015).…”
Section: Damsmentioning
confidence: 99%